Case report: Successful multimodal assessment and management of chemothorax - Panza, Teodora; Quercia, Rosatea; Signore, Francesca; De Iaco, Giulia; Brascia, Debora; Sampietro, Doroty; Gasbarro, Anna Rita; Dell’Aera, Maria; Lorusso, Vito; Marulli, Giuseppe; De Palma, Angela (Frontiers in Surgery, 2022)
Dislocation or wrong placement of central venous catheters into the pleural cavity is rare, but if undiagnosed, may cause major, sometimes life-threatening, complications (pneumothorax, hemothorax, infection, migration) and accidental pleural effusion due to intravenous injection of fluids containing drugs (i.e. chemotherapy, antibiotics, parenteral nutrition, other). We report a rare case of pleural effusion consisting of chemotherapy (chemothorax) directly injected into the pleural cavity due to the wrong placement of a central venous catheter (Porth-A-Cath) in a woman with breast cancer. A multidisciplinary management consisting in antidote administration followed by removal of the venous device and washing of the pleural cavity through video-assisted thoracic surgery (VATS) avoided any major complication related to the adverse event.